2011
DOI: 10.1111/j.1475-5661.2011.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Positivism, post‐positivism and domestic water demand: interrelating science across the paradigmatic divide

Abstract: The contributions and limitations of the positivist and post-positivist approaches to research into domestic water demand are analysed and compared, and the potential for bringing the two perspectives together is evaluated. The analysis is based on a 4-year investigation of water demand conducted as part of a larger multidisciplinary research programme on sustainable urban environments and specifically the role of water in new developments. The positivist approach is more traditional and offers immediate utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Whilst a number of studies have forecast that water consumption will rise in the future (eg, Sharp et al 2011; Environment Agency no date), others have shown that, although domestic demand measured over the long term has risen, there has been a decline in consumption in recent years which may be as a result of a wider take up of metering . The metering hypothesis behind the fall in consumption is difficult to prove however, and it could be reflective of a fall in consumption of other material goods in the UK over the past 10 years (Goodall 2011).…”
Section: The Importance Of Letting Go Of Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst a number of studies have forecast that water consumption will rise in the future (eg, Sharp et al 2011; Environment Agency no date), others have shown that, although domestic demand measured over the long term has risen, there has been a decline in consumption in recent years which may be as a result of a wider take up of metering . The metering hypothesis behind the fall in consumption is difficult to prove however, and it could be reflective of a fall in consumption of other material goods in the UK over the past 10 years (Goodall 2011).…”
Section: The Importance Of Letting Go Of Watermentioning
confidence: 99%
“…Of course, some authors (eg, Sharp et al 2011;Strengers 2011) caution that research approaches to water demand management which rely on prediction and forecasting cannot be reasonably integrated with approaches that challenge the status quo of the system such as the perspective we have identified in the previous sections. Sharp et al (2011) using UK water management examples referred to the incompatibility of approaches that challenge the status quo with approaches and methodologies that are deeply embedded in existing policy and practical processes for water demand management such as the micro-components approach, or forecasting approaches used by water companies (Sharp et al 2011).…”
Section: Distributed Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Pohl (2005) and Sharp et al, (2011) suggest that there is a value in 'inter-relating interdisciplinarity' (Pohl 2005) in which contrasting disciplines work towards a mutually intelligible body of knowledge (Gandy 2008, p. 566). It remains unclear exactly how 'interrelating interdisciplinarity' transfers to the collaborative research arena that includes scientists and practitioners.…”
Section: Introduction and Contextmentioning
confidence: 99%
“…A number of commentators have raised questions about whether paradigmatically different approaches can work together (Pohl 2005, Evans and Marvin 2006, Connelly and Anderson 2007, Sharp et al 2011). The argument is that diverse viewpoints cannot necessarily be integrated to form a single new form of knowledge.…”
Section: Introduction and Contextmentioning
confidence: 99%